Cover Feature: On Pentakis(pentafluoroethyl)stannate, [Sn(C2F5)5]−, and the Gas‐Free Generation of Pentafluoroethyllithium, LiC2F5 (Chem. Eur. J. 8/2018). Issue 8 (13th December 2017) - Wiesemann, Markus; Klösener, Johannes; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract : Gas‐free generation of pentafluoroethyllithium : Perfluoroalkylation reactions are often characterized by the tedious handling of gases which lead to the development of numerous easy‐to‐handle perfluoroalkylation reagents. In the course of this the hypervalent [PPh4 ][Sn(C2 F5 )5 ] represents an easily accessible, storable and solid precursor for the generation of the highly reactive LiC2 F5 . Its reactivity and the separation of tin‐containing byproducts were proven in pentafluoroethylation reactions. More information can be found in the Full Paper by B. Hoge et al. onpage 1838 .